Towards Achieving Equity and Innovation in Newborn Screening across Europe - Sikonja, Jaka; Groselj, Urh; Scarpa, Maurizio; la Marca, Giancarlo; Cheillan, David; Kölker, Stefan; Zetterström, Rolf H; Kožich, Viktor; Le Cam, Yann; Gumus, Gulcin; Bottarelli, Valentina; van der Burg, Mirjam; et al. (International journal of neonatal screening, 2022)
Although individual rare disorders are uncommon, it is estimated that, together, 6000+ known rare diseases affect more than 30 million people in Europe, and present a substantial public health burden. Together with the psychosocial burden on affected families, rare disorders frequently, if untreated, result in a low quality of life, disability and even premature death. Newborn screening (NBS) has the potential to detect a number of rare conditions in asymptomatic children, providing the possibility of early treatment and a significantly improved long-term outcome. Despite these clear benefits, the availability and conduct of NBS programmes varies considerably across Europe and, with the increasing potential of genomic testing, it is likely that these differences may become even more pronounced. To help improve the equity of provision of NBS and ensure that all children can be offered high-quality screening regardless of race, nationality and socio-economic status, a technical meeting, endorsed by the Slovenian Presidency of the Council of the European Union, was held in October 2021. In this article, we present experiences from individual EU countries, stakeholder initiatives and the meeting's final conclusions, which can help countries attempting to establish new NBS programmes or expand existing provision.